Time to Finger Point or Fix? An Invitation to Join Ongoing Efforts to Promote Ethical Authorship and Other Good Publication Practices. (July 2013) - Woolley, Karen L; Gertel, Art; Hamilton, Cindy W; Jacobs, Adam; Snyder, Gene P; ,
In this commentary, we present evidence that unethical authorship (eg, guest and ghost authoring) and other publication practices are not restricted to the pharmaceutical industry; they also occur in academia. Such practices are not an industry problem—they are a research problem. To enhance trust in industry-sponsored research, companies have made rapid and far-reaching changes to their publication guidelines, policies, and procedures. Professional medical writers have adopted, and continue to implement, these changes. Although evidence indicates that industry practices are improving, there is certainly more to do, both in industry and academia. We invite readers to join ongoing efforts to promote ethical publication practices.